Colon irrigation and quality of life in patients with colostomy - Francisco Javier Barbero Juárez; Francisco José Martín Cañete; Vicenta Galbis Valero; Josefa García López (Fundación para el Desarrollo de la Enfermería, 2004)
One of the most important problems that a patient with a colostomy has to face after surgery is the intestinal continence. This lead these patients to experience not only a series of physical changes but also hygienic, dietetic, social, etc. As nurses, we must learn how to detect the needs of these patients in order to offer them an appropriate attention to improve their quality of life. Our aim is to assess if the irrigation technique (IT) as a method for intestinal continence improves the quality of life in these patients. Methodology: A Pretest-postest study without control group was carried out in order to evaluate the usefulness of IT to improve the quality of life in patients with colostomy. Following a normalized protocol, the technique was taught to patients whose quality of life was evaluated before and after the application of IT. Results: Quality of life rate before intervention was 54,2% and reached 77,3% (statistically significant) once the patient has used IT for two months. Conclusions: IT is associated with a remarkable improvement in the quality of life of patientes with colostomy. This improvement is reflected in the eight dimensions analysed: psychological welfare, physical welfare, body image, pain, sexual activity, nutrition, social preoccupations and device handling.